Analysis of changes in the special teaching career regime, with the implementation of the decree 1278 of 2002 against decree 2277 of 1979, in professionalization, ladder, evaluation and remuneration of the teacher in Colombia (2019)
The following essay is an approach to the system of special teaching career in Colombia, through two of its statutes, the decrees Law 2277 of 1979 and 1278 of 2002, respectively, which organizes the exercise of this profession in the education sector. An approach is made to the normative framework of the teaching career; Next, we refer to the changes that are drawn up in each of the decrees Laws in aspects such as income, promotion, remuneration and evaluation; Below are the results and changes in the changes, to get to define how significant they have been for the structuring of the teaching profession.